ALAT PENDETEKSI WARNA BUAH UNTUK PENYANDANG BUTA WARNA - Anada, Dea; Rizastiani, Rizastiani; Ocsirendi, Ocsirendi; Khasanah, Nur (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This research uses quantitative data analysis by applying the hardware design method. The hardware system consists of a TCS3200 sensor circuit based on an Arduino Uno microcontroller. Color sensor to detect object color and 16x2 LCD to display output in the form of information on the type of color detected. This research aims to detect colors to help people with color blindness, this tool is able to detect 3 colors in RGB space. Based on the overall test results that the color sensor reading will always depend on the ambient light intensity and the distance between the sensor and the object. However, this tool has been successfully designed and can work properly and correctly as desired. In this study, testing on patients with color blindness cannot be said to be effective because there are still people with color blindness who fail to use the tool.